Evaluating the Role of Extractives in Biomass Pyrolysis for Enhanced Hydrogen Syngas Production - Suprianto, Teguh; Muhammad Kasim; Darmansyah (Science and Technology Research Centre Universitas PGRI Semarang, 2025)
This study explores how extractive content in lignocellulosic biomass affects syngas quality during fixed-bed pyrolysis-gasification, specifically focusing on hydrogen (H₂) concentration. While woody biomass is a known energy source, the link between its non-structural organic compounds (extractives) and H₂ in syngas is often overlooked. We investigated teak, coconut, and jackfruit wood to understand this influence and optimize temperature for better biomass-to-hydrogen conversion. An MQ-8 sensor detected H₂ levels. Results show that biomass with high extractive content significantly boosts syngas H₂. Jackfruit wood yielded the highest H₂ concentration (2898 ppm at 471°C), outperforming coconut wood (1965 ppm at 444°C) by 41.7% and teak wood (1931 ppm at 395°C) by 50.1%. This is due to jackfruit's high cellulose and extractive content, which decompose efficiently at higher temperatures. Overall, high-extractive biomass improves syngas quality and expands sustainable options for hydrogen production.